Op HERRICK Primary Care Casualties: The Forgotten Many. Issue 3 (1st September 2012) - Nelson, Toby; Wall, C; Driver, J; Simpson, R
Abstract : Objective: The number of battle casualties generated during war is far outnumbered by non-battle casualties. Each year the current conflict in Afghanistan sees hundreds of service personnel medically evacuated direct from the front line to the care of their home units' primary care facility. To date these casualties remain undiscovered by medical research. This is the first study to look at the care pathway of primary care casualties from Operation HERRICK using information from the Defence Patient Tracking System (DPTS). Methods: Information relating to all casualties from Afghanistan discharged at the airhead between 1 January 2009 and 31 December 2010 was collected from the DPTS. Common conditions were identified and information relating to the follow up care extracted to provide an overview of the care pathway. Results: 387 aeromedical evacuations were identified as primary care casualties. The three commonest conditions were musculoskeletal (183 cases), mental health (29) and noise-induced hearing loss (26). 205 (53%) were not seen outside of primary care for the tracked condition. 166 (81%) of those that remained under primary care had two or less consultations during the time period of the study. The mean time frame between the 1st and 2nd consultation was 5.4 weeks. Conclusions: A significant number of aeromedical evacuations from Afghanistan are for primary care casualties. The DPTS can be used to provide a basic overview of the care pathway of repatriated personnel. Little contact with the medical services would appear to occur for these types of casualties. There is a significant gap in military medical research looking at primary care casualties repatriated from operations.